104k views
3 votes
I dont get this please help me on this thanks​

I dont get this please help me on this thanks​-example-1

2 Answers

3 votes

Answer:

X=-2

Explanation:

1. -4(x-7)=36

Devide both side of the equation by -4

2. X-7=-9

X-7=-9

x=-9+7

Move constant to the right side and change its sign

3. x=-9+7

Calculate the sum, And You Will Get x=-2

User Indiano
by
6.0k points
1 vote

Answer:

x=-2

Explanation:

-4(x-7)=36

divide both sides by four

x-7=-9

move constant to the right and change its sign

x=-9+7

calculate the sum

x=-2

User Elmazzun
by
6.2k points